The Impacts of Customer Perceived Value on Customer Satisfaction: An Empirical Study in Bank of Ceylon - Sathana, V. (University of Kelaniya, 2011)
In a competitive setting, satisfying customers is only the base line, Management should focus on gaining the consumer satisfaction with the customer perceived value through quality service for increasing customer expectation. This research intentionally focuses on the relationships and impact among customer perceived value and customer satisfaction, that is the proposed model indicates that delivering high quality service and creating superior customer value can result in achieve high customer satisfaction, ultimately leading to consumer retention. Customer perceived value and Custom satisfaction data were collected from 500 customers of retail-banking in Jaffna District by using structured questionnaires. Customer perceived value is analyzed through the benefits and cost of the service, then the benefits and cost were assessed by the product offering, customer services, relationship, image, buy price and other cost. Simple correlation measures is used to examine the hypothesized relationships between perceived quality, customer expectation,perceived value and customer satisfaction and also to increase the internal validity of the results, simple regression measures of customer perceived value and customer satisfaction were examined. An important finding of this study that since customer satisfaction is related to customers' perceived value, banks should endeavor to satisfy every customer. Banks would be wise to target and serve only those customers whose needs it can meet better than its competitors in a valuable manner. The customers who are most likely to remain with that bank for long periods, which will purchase multiple products and services, who will recommend the bank to their friends and relations, finally it crates the business success. The customer's perception of value drives the customer's behavior. The greater the perceived value of an offering versus the customer's alternatives, the more likely the customer is to make a decision to select the particular offering.
Keywords: Perceived Quality; Customer Expectation; Customer Perceived Value; Customer Satisfaction; Customer Loyalty